Effects of Aging on Levo-Dihydroxyphenylalanine- Induced Dyskinesia in a Rat Model of Parkinson’s Disease - Nishijima, Haruo; Kimura, Tamaki; Mori, Fumiaki; Wakabayashi, Koichi; Kinoshita, Iku; Nakamura, Takashi; Kon, Tomoya; Suzuki, Chieko; Tomiyama, Masahiko (Frontiers in Aging Neuroscience, 2021)
Background It remains unclear why patients with young-onset Parkinson’s disease more often develop levo-dihydroxyphenylalanine (L-dopa)-induced dyskinesia (LID) and have a more severe form than patients with old-onset Parkinson’s disease. Previous studies using animal models have failed to show young-onset Parkinson’s disease enhances LID. Objectives To evaluate the association of age at dopaminergic denervation (onset age) and initiation of L-dopa treatment (treatment age) with LID development in model rats. Methods We established rat models of young- and old-lesioned Parkinson’s disease (6-hydroxydopamine lesions at 10 and 88 weeks of age, respectively). Dopaminergic denervation was confirmed by the rotational behavior test using apomorphine. Rats in the young-lesioned group were allocated to either L-dopa treatment at a young or old age, or saline treatment. Rats in the old-lesioned group were allocated to either L-dopa treatment or saline group. We evaluated L-dopa-induced abnormal involuntary movements during the 14-day treatment period. We also examined preprodynorphin mRNA expression in the striatum (a neurochemical hallmark of LID) and the volume of the medial globus pallidus (a pathological hallmark of LID). Results LID-like behavior was enhanced in L-dopa-treated young-lesioned rats compared with L-dopa-treated old-lesioned rats. Preprodynorphin mRNA expression was higher in L-dopa-treated young-lesioned rats than in in L-dopa-treated old-lesioned rats. The volume of the medial globus pallidus was greater in L-dopa-treated young-lesioned rats than in L-dopa-treated old-lesioned rats. Treatment age did not affect LID-like behavior or the degree of medial globus pallidus hypertrophy in the young-lesioned model. Conclusion Both dopaminergic denervation and L-dopa initiation at a young age contributed to the development of LID; however, the former may be a more important factor.